Quaternary Stratigraphy in Northwestern Maine: A Progress Report - Lowell, Thomas; Becker, Dale; Calkin, Parker (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTA preliminary Quaternary stratigraphy for northwestern Maine can be assembled from interpretation of ice-flow indicators (dispersal and erosional), exposed sections, and drill-hole logs. Evidence from the ice-flow indicators delineates at least four regions each with different ice-flow histories. The distribution of these regions may result from an eastward invasion of Laurentide source ice during the early portion of the late Wisconsinan and subsequent development of a local ice dome during the closing portion of the Late Wisconsinan substage. Exposed sections contribute the following probable sequence of events to the stratigraphy: 1) deposition of alluvial fans, 2) deposition of a gray compact till beneath eastward flowing (Laurentide) ice, 3) deposition of a brown till beneath northward flowing local ice, 4) deglaciation by a southward retreating ice margin. These events appear continuous and have all been provisionally assigned a Late Wisconsinan age. Drill-hole logs confirm the sequence derived from the exposed sections and allow extension of the Quaternary stratigraphy. The drill-log data show three associated groups of sediments that may in turn result from at least three separate ice margin advances and recessions. The uppermost group of sediments is correlated with those found in exposed sections. The position of the drill-hole logs in an over-deepened basin suggest erosion by at least one even earlier glaciation.